2003
DOI: 10.1021/bp034022b
|View full text |Cite
|
Sign up to set email alerts
|

Direct Current Electrical Field Effects on Intact Plant Organs

Abstract: Intact plant tissues (of hypocotyls, radicles, cotyledons and leaves) were contracted by applying a low DC electrical field through them. Stomatal opening as a result of the electrical treatment of leaves was observed, presumably due to the differential influence of the electrical treatment on guard cell turgor pressure versus turgor pressure of the surrounding epidermal cells. In addition, leakage of minerals from the treated leaves was detected (higher contents of potassium, sodium, calcium and sulfur), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…In our work, the maximal field strength was 10 V/m, which was too low to cause electroporation; in addition, the ''permeability'' lasted for several days, because the maximal amount of extracellular Tc and phenolics was reached 3 days after PEF treatment, which was completely different from the transient response time for electroporation reported by Angersbach et al (2000). Ganeva et al (2002) and Zvitov et al (2003) also reported that application of electrical field to yeast or plant tissues led to leakage of intracellular substances to the surrounding medium. In addition, our experimental results show that the amount of extracellular Tc and phenolics decreased rapidly after day 3 (Table I).…”
Section: Discussioncontrasting
confidence: 73%
“…In our work, the maximal field strength was 10 V/m, which was too low to cause electroporation; in addition, the ''permeability'' lasted for several days, because the maximal amount of extracellular Tc and phenolics was reached 3 days after PEF treatment, which was completely different from the transient response time for electroporation reported by Angersbach et al (2000). Ganeva et al (2002) and Zvitov et al (2003) also reported that application of electrical field to yeast or plant tissues led to leakage of intracellular substances to the surrounding medium. In addition, our experimental results show that the amount of extracellular Tc and phenolics decreased rapidly after day 3 (Table I).…”
Section: Discussioncontrasting
confidence: 73%
“…When the electric field strength was higher than 70 kV/cm, the color value decreased slowly with the increased electric field strength. Direct current electric field can destroy the micro-structure of vegetable (Zvitov, Schwartz, Zamski, & Nussinovitch, 2003). Thus, the higher electric field strength may destroy the micro-structure which can protect chlorophyll which is not to be destroyed.…”
Section: Resultsmentioning
confidence: 99%
“…[16,17]. To improve the betalain extraction, some of the pretreatment methods have been proposed, such as pulsed electric fields [18], gamma irradiation [8], and low-direct current electric fields [19]. But, such methods are quite expensive when compared to the solvent extraction techniques.…”
Section: Extraction Techniquesmentioning
confidence: 99%